A theology of reconstruction: nation-building and human rights - Villa-Vicencio, Charles (Cambridge studies in ideology and religion, 1992)
The changing situation in South Africa and eastern Europe prompts Charles Villa-Vicencio to investigate the implications of transforming liberation theology into a theology of reconstruction and nation-building. Such a transformation, he argues, requires theology to become an unambiguously inter-disciplinary study. This book explores the encounter between theology, on the one hand, and constitutional writing, law-making, human rights, economics, and the freedom of conscience on the other. Locating his discussion in the context of the South African struggle, the author compares this situation to that in eastern Europe, and the challenge of what is happening in these situations is identified for contexts where 'the empire has not yet crumbled'.